Efficient Design Methodology for a Complex DRA-SIW Filter-Antenna Subsystem - Umair Naeem; Amjad Iqbal; Muhammad Farhan Shafique; Stéphane Bila (International Journal of Antennas and Propagation)
This work reports on an efficient design methodology for realizing hybrid filter-antenna subsystems. Designing a filter-antenna subsystem in the case of complex multimode filter is not straightforward. The coupling of the antenna with a multimode filter depends upon several uncorrelated parameters. An efficient design methodology is proposed which can address these complex problems. The work focuses on the characterization of radiating and filtering elements and then proposes a reliable model, which is derived mathematically as well as from rigorous statistical analyses, which can then be used for designing hybrid filter-antenna structures such as a hybrid DRA codesigned with a SIW based multimode filter. A highly compact filter-antenna subsystem has been designed employing the proposed methodology, and the measured results validate the proposed design technique.